COVID-19 and Chagas Disease in Buenos Aires, Argentina - Fernandez, Marisa Liliana; Benchetrit, Andres; Astudillo, Osvaldo German; Garay, Alejandra M.; De Vedia, Lautaro; Garcia Bournissen, Facundo; Lloveras, Susana Cristina; Orduna, Tomas Agustín; Gonzalez, Gustavo Daniel (Frontiers in Tropical Diseases, 2022)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2. COVID-19 leads, in most patients, to mild-to-moderate symptoms, but some develop severe disease and succumbed to death. People with medical conditions have a higher risk of death than those without them. Chagas disease (CD) can cause cardiac diseases in approximately one-third of affected people. The aim of this study is to find out if there is any clinical association between Chagas disease and COVID-19 severity. This is a cohort study of 29 patients who were hospitalized with COVID-19 and had a diagnosis of chronic Trypanosoma cruzi infection. This coinfected cohort was matched by sex, age, presence of comorbidities, and requirement of hospitalization on intensive care unit (ICU) at admission with a control cohort of patients hospitalized due to COVID-19 without CD in a 3:1 ratio (n = 87). The clinical outcomes evaluated were as follows: days of hospitalization, death, and requirement of ICU and mechanical respiratory assistance (MV). The study protocol was approved by the Institutional Ethics in Research Committee. The Chagas disease/COVID-19 coinfected cohort had a median age of 55 years old (49.0, 66.0); 17 (59%) were male. All patients survived the acute COVID-19. Three of them were admitted to the ICU, and two required MV. Twenty-two (75.8%) required supplemental oxygen. There were no statistical differences in any laboratory parameters between the groups except for lactic acid dehydrogenase, which showed higher levels in the coinfected cohort, with a median of 573 U/L (interquartile range: 486.00, 771.00) vs. 476 U/L (346.00, 641.00) in the control group (p = 0.007). There were no differences in clinical outcomes between both groups. On the cohort with Chagas disease, there were zero deaths, three (10.3%) were admitted in the ICU, and two (6.9%) required MV, while for the control group there were six deaths (6.6%), 13 required ICU (14.9%), and 11 required MV (12.6%), without a statistically significant difference. This small series of coinfected Chagas disease and COVID-19 does not suggest differences in clinical evolution compared to non-Chagas patients. This data is similar to a Brazilian cohort. More data of this population with and without cardiomyopathy is needed to optimize the follow-up and recommendation for the population affected by this neglected tropical disease about COVID-19.